UPAYA PENCITRAAN APOTEK DAN KERAGAMAN PRODUK UNTUK MENINGKATKAN PENJUALAN MELALUI KEPUTUSAN PEMBELIAN - Mukti Kemarauana; Rafadi Khan Khayru; Fayola Issalillah (Jurnal Ilmiah Satyagraha, 2022)
Retail business competition is currently getting tougher. This is becausethe retail business is a picture of economic development. To face this competition,marketing management needs to know how consumers make purchasing decisions.Marketing management needs to know the right way so that consumers decide tobuy at the store. This study aims to determine the effect of pharmacy image andproduct diversity to improve purchasing decisions. The population of thisquantitative study are consumers from one of Kimia Farma's pharmacies in thecity of Surabaya in East Java. The number of populations cannot be determined,therefore the researcher used 100 respondents as the research sample. This studyuses multiple linear regression analysis techniques. The results of this studyindicate that the image of the pharmacy has a significant influence on researchdecisions. Furthermore, it is proven that purchasing decisions made by consumersare influenced by the variety of products provided. Together, the image of thepharmacy and the diversity of products have a significant influence on consumerpurchasing decisions.